Opposing Reality in 3 Short Stories by Shirley Ren The Pink Umbrella (2019), Jason Sanford The Eight-Thousanders (2020), and Alyssa Wong A Fist of Permutations in Lightning and Wildflowers (2016) - Sari Septriyani; Desvalini Anwar (English Language and Literature, 2023)
This research is an analysis of 3 short stories by Shirley Ren The Pink Umbrella (2019), Jason Sanford The Eight-Thousanders (2020) and Alyssa Wong A Fist of Permutations in Lightning and Wildflowers (2016). This research discusses about defense mechanisms applied to oppose reality. Defense mechanisms are commonly used in everyday life, a person applies defense mechanisms when the ego can no longer balance the id and superego and worries arise in the person. However, if this is done to oppose reality, it will cause new prolonged conflict. This research uses a descriptive qualitative method which is using psychoanalysis theory by Sigmund Freud which deals with opposing reality and defense mechanisms. This research aims to find out what types of defense mechanism applied by character and how the symptoms appear. The analysis of this study revealed that the character applies 2 defense mechanisms, namely denial and displacement, to oppose reality and the symptoms that arise. The conclusion of this study is defense mechanisms applied to oppose reality is not good, not to change things that are not desirable but to cause new prolonged conflicts. Opposing reality means not being able to come to terms with reality and not being able to come to terms with one self so that as a result the characters go through life in misery.